Wetland‐Scale Mapping of Preferential Fresh Groundwater Discharge to the Colorado River. Issue 5 (2nd April 2019) - Briggs, Martin A.; Nelson, Nora; Gardner, Philip; Solomon, D. Kip; Terry, Neil; Lane, John W.
Abstract: Quantitative evaluation of groundwater/surface water exchange dynamics is universally challenging in large river systems, because existing methodology often does not yield spatially‐distributed data and is difficult to apply in deeper water. Here we apply a combined near‐surface geophysical and direct groundwater chemical toolkit to refine fresh groundwater discharge estimates to the Colorado River through a 4‐km 2 wetland that borders the town of Moab, Utah, USA. Preliminary characterization of raw electromagnetic imaging (EMI) data, collected by kayak and by walking, was used to guide additional direct‐contact electrical measurements and installation of new monitoring wells. Chemical data from the wells strongly supported the EMI spatial characterization of preferential fresh groundwater discharge embedded in natural brine groundwaters and weighted to the southern wetland section. Inversion of the EMI data revealed sub‐meter scale detail regarding bulk electrical conductivity zonation across approximately 15.5 km of transects, collected in only 3 days. This electrical detail indicates processes such as salinization of the unsaturated zone and direct discharge through the Colorado River sediments and a tributary creek bed. Overall, the study contributed to a substantial reduction in fresh groundwater discharge estimates previously made using sparse existing well data and a simplified assumption of diffuse fresh groundwater discharge below the entire wetland. EMI will likely become a widely used tool in systems with natural electrical contrast as groundwater/surface water hydrogeologists continue to recognize the prevalence of preferential groundwater discharge processes.